Benchmark for Country-Level Earthquake Strong-Motion Instrumentation Program - Prakoso, Widjojo Adi; Sukanta, I Nyoman (Makara Journal of Technology, 2012)
An empirical study to develop benchmark models at country-level to assess the suggested number of earthquake strongmotion stations based on a framework encompassing geographic, demographic, and socio-economic parameters is reported. The models are to provide a working estimate of the required number of stations for improving the strongmotion instrumentation program of Indonesia. National earthquake strong-motion networks of New Zealand, Japan, Taiwan, Iran, Turkey, and Italy were used as the references. The parameter proposed is the number of stations in land area of 1,000 km2, and three models based on the exponential regression analysis are presented as functions of population density, Gross Domestic Product (GDP) per capita, and the Global Competitiveness Index (GCI) Basic Requirements Index. Using the models, it is suggested that Indonesia would require at least 750 stations.